Inter-ethnic relations of teenagers in England's schools: the role of school and neighbourhood ethnic composition - Simon Burgess; Lucinda Platt (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2018)
The paper presents an empirical analysis of inter-ethnic relations among adolescents in England's schools, the first national study of schools throughout England to relate inter-ethnic attitudes to both school and area ethnic composition. We combine survey data on 'warmth' of feeling for specific ethnic groups, friendships and attitudes with administrative data on the shares of those groups at school and area level. We confirm that the pupils have warmer feelings for their own ethnic group than for others. Second, we show that in schools with more pupils from another ethnic group the gap between a pupil's views of those from her own group and from another ethnic group is smaller. This is true for attitudes of the majority and of minority ethnic groups. Third, we show that school composition (interpreted as contact) mitigates area composition (interpreted as exposure).
Keywords: 330